Meningkatkan Kemampuan Berbicara Bahasa Sunda Anak Melalui Metode Ngadongeng di Paud Ibnu Abbas Kabupaten Cianjur - Ucu Nuryati; Ibnu Hurri; Elnawati Elnawati (PT. Alahyan Publisher Sukabumi, 2025)
Initial observations conducted by researchers found that the Sundanese speaking skills of children at Ibnu Abbas Preschool were not yet fluent, and they also showed little interest and knowledge about Sundanese traditions and culture. Many children did not understand Sundanese well. They lacked vocabulary and were not fluent in Sundanese. Therefore, early childhood requires familiarization and guidance from adults to provide the necessary knowledge for their future, enabling them to use Sundanese to communicate with their parents, community, and friends. Based on these findings, researchers wanted to improve Sundanese speaking skills through the ngadongeng method. This study used a Classroom Action Research method with two cycles of action. During the initial observation, the children's Sundanese speaking ability was only 33.14%. Then, there was an increase of 17% to 50%. After the intervention in the second cycle, the improvement in speaking ability optimally increased to 78.85%. There were obstacles encountered in the implementation of storytelling techniques, namely, the teacher's lack of thoroughness in selecting the title and characters of the stories being read, thus not capturing children's attention. Furthermore, the teacher also lacked interaction and explanation during each story telling, using language that children may not have heard often, resulting in children not understanding the content of the story. However, these obstacles were resolved, and in the implementation of cycle II, these obstacles were eliminated. Therefore, the storytelling method used by the researcher was able to improve Sundanese speaking skills in children at Ibnu Abbas Early Childhood Education (PAUD).